Utilization of Bioetanol Fermentation Waste Pineapple and Coconut Water as Disinfectants With Bacteria Saccharomyces Cerevisiae - Rizka Lestari Dewi Rizka; Anggun Puspitarini Siswanto (Eduvest - Journal of Universal Studies, 2021)
Research analysis of sugar content and the effect of ethanol content on bioethanol from old coconut water and pineapple peel with the help of Saccharomyces Cerevisease bacteria. The condition of the spread of the Corona Virus or COVID-19 in Indonesia, thus making bioethanol produced from fermenting pineapple peel waste and old coconut water for disinfectant products to spray around homes and public places to reduce bacteria and viruses. The production of bioethanol is carried out by pre-treating coconut water and pineapple peel, the fermentation stage with Saccharomyces cerevisiae yeast and the distillation stage. The result of the highest bioethanol content was 32% with a mass of 5 g yeast with a time of 24 hours. The highest calorific value at 72 hours was 211.95 kcal/kg. The result of the highest specific gravity at 24 hours and the mass of yeast 4 g is 0.98 g/ml. Based on the bioethanol quality requirements, the bioethanol produced is not in accordance with the bioethanol quality requirements, this is due to the absence of nutrient decomposing bacteria so that it is less than optimal in converting glucose into bioethanol.